Correlation of Nitrite and Ammonia with Prevalence of Enterocytozoon hepatopenaei (EHP) in Shrimp (Litopenaeus vannamei) on Several Super-Intensive Ponds in East Java, Indonesia - Anord Charles Nkuba; Gunanti Mahasri; Nunuk Dyah Retno Lastuti; Adamu Ayubu Mwendolwa (Faculty of Fisheries and Marine Universitas Airlangga, 2021)
AbstractEnterocytozoon hepatopenaei (EHP), a microsporidia parasite known to hinder shrimp growth by infecting its hepatopancreas, is recently an emerging infection for Litopenaeus vannamei farms in Indonesia. The present study was conducted to investigate the relationship between nitrite and ammonia concentration with EHP infection in the super-intensive ponds. Shrimps and water samples were collected from six ponds in aquaculture super-intensive ponds with a stocking density of 5,000 shrimps in each pond which is located in Pasuruan, Lamongan, and Tuban Regency, Indonesia. The water sample was taken to the laboratory for the measurement of ammonia and nitrite. The samples of ammonia and nitrite were detected by spectrophotometer, and the PCR was used to detect 18S rRNA of EHP. The PCR analysis that showed two positive samples of L. vannamei, from the ponds with a high concentration of ammonia and nitrite, were infected by EHP. The statistical analysis showed a significant correlation between ammonia and nitrite with the prevalence of EHP infections, where the Pearson correlation (r) was 0.980 and 0.943, respectively. There was a high prevalence of EHP infection with the increase in nitrite concentration and ammonia in pond four and pond six. The concentration of over 1mg/l of ammonia and nitrite could influence EHP infection prevalence in the shrimp farms. Highlight ResearchAmmonia and nitrite concentration influence the prevalence of Enterocytozoon hepatopenaei infection in Super intensive ponds.The estimated prevalence of Enterocytozoon hepatopenaei was 16.7%.PCR amplification analysis was used to detect the 18S ss-rRNA of Enterocytozoon hepatopenaei and 510-bp was obtained.